1990
DOI: 10.1002/jmor.1052040207
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in the oocyte and its surrounding vestments during in vivo fertilization in the dasyurid marsupial sminthopsis crassicaudata

Abstract: This light and transmission electron microscopical study shows that the first polar body is given off before ovulation and that part of its cell membrane and that of the surrounding oocyte have long microvilli at the time of its ejection. Several layers of cumulus cells initially surround the secondary oocyte and first polar body, but the ovulated oocytes in the oviducts in the process of being fertilized do not have cumulus cells around them. Partly expelled second polar bodies occur in the oviduct; they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 20 publications
5
30
0
Order By: Relevance
“…This mechanism has been demonstrated in A. agilus (= A. stuartii) [Selwood, 1994] and in T. vulpecula ] and is probably widespread in marsupials because similar vesicular arrays are a common feature in peripheral cytoplasm of other marsupials at the time of cell-cell or cell-zona adhesion, e.g. in Macropus eugenii [Renfree and Lewis, 1996], S. crassicaudata [Breed and Leigh, 1990]. Time-lapse studies of cleavage in A. agilus and S. macroura [Selwood and Smith, 1990] release of the vesicular arrays occurs at specific times in the cell cycle, immediately before and after M phase.…”
Section: Zona Pellucidamentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism has been demonstrated in A. agilus (= A. stuartii) [Selwood, 1994] and in T. vulpecula ] and is probably widespread in marsupials because similar vesicular arrays are a common feature in peripheral cytoplasm of other marsupials at the time of cell-cell or cell-zona adhesion, e.g. in Macropus eugenii [Renfree and Lewis, 1996], S. crassicaudata [Breed and Leigh, 1990]. Time-lapse studies of cleavage in A. agilus and S. macroura [Selwood and Smith, 1990] release of the vesicular arrays occurs at specific times in the cell cycle, immediately before and after M phase.…”
Section: Zona Pellucidamentioning
confidence: 99%
“…It appears to be the initial site of sperm egg binding. In the species examined, the zona pellucida provides a barrier to polyspermy in didelphid marsupials but not in dasyurid marsupials [for review, see Breed, 1996] in which polyspermy in vivo has been observed in Antechinus stuartii (= A. agilus) [Selwood, 1982] and S. crassicaudata [Breed and Leigh, 1990]. …”
Section: Zona Pellucidamentioning
confidence: 99%
“…Ovarian stimulation in the fat-tailed dunnart maintaining cellular processes from granulosa cells that form gap and tight junctions through the zona pellucida for endocrine and nutritional support of the oocyte (Breed & Leigh 1990). This was not observed in more mature GOC in preparation of the complete removal of granulosa cells prior to ovulation (Breed & Leigh 1988).…”
Section: Timetable Of Events In Natural Cyclesmentioning
confidence: 99%
“…Oocytes maturation and in vitro fertilization studies in marsupials, especially Dasyuridae, were described by Selwood, (1982), Breed & Leigh, (1990), Breed, (1996 and Hickford et al (2001). Kress et al described the oogenesis pattern in Sminthopsis macroura and found that the timetable of oogenesis is accelerated as in other marsupials showing relatively early female maturation.…”
Section: Introductionmentioning
confidence: 98%